Charlson Comorbidity Index Predicts 5-Year Survivorship of Surgically Treated Hip Fracture Patients. (2nd November 2018) - Jiang, Lei; Chou, Andrew Chia Chen; Nadkarni, Nivedita; Ng, Caris En Qi; Chong, Yun San; Howe, Tet Sen; Koh, Joyce Suang Bee
Introduction: This study aims to assess the correlation of the age-adjusted Charlson comorbidity index (ACCI) with 5-year mortality in a surgically treated hip fracture population. Materials and Methods: A retrospective analysis was performed on 1057 patients aged 60 years and above who underwent surgery for hip fracture with a minimum of 5-year follow-up (92.2% 5-year follow-up rate) in a tertiary hospital. Manual review of patients' electronic hospital records was performed to record demographic data, comorbidities, and length of stay. Mortality data were extracted from the hospital's electronic medical records and corroborated with the National Electronic Health Record. Results: Of the 1057 patients, 283 (26.8%) were male. The majority of patients were 80 years of age and above (42.5%), with the oldest patient operated on age 102 with a mean age of 77.8 (8.6) years. Four hundred eighteen (39.5%) patients sustained extracapsular intertrochanteric fractures. The mean follow-up duration was 8 years and 3 days with an overall survivorship of 37.2%. A multiple regression model constructed with ACCI, age, gender, and fracture pattern demonstrated satisfactory predictive ability with a concordance statistic of 0.68. Patients with a higher ACCI category (≥6) had an increased 5-year mortality rate (41.8%) with an odds ratio of 13.6 (6.7-31.8, P < .001) compared to those with an ACCI category of 3 and below (89.3%). Discussion: The study demonstrates that ACCI correlated with 5-year mortality after surgical treatment of hip fracture. This information is pertinent in the counseling of patients with regard to their midterm survival following hip fracture surgery and may inform policy makers of the varied midterm survival rates in patients with differing ACCI scores and educate the allocation of health-care resources. Conclusion: The ACCI correlates with 5-year mortality after surgical treatment of hip fracture.